International business - Paul, Justin (Prentice-Hall of India Private Limited, 2005)
International Business by Justin Paul provides a comprehensive introduction to the complex and dynamic world of business conducted across national borders. The book explores how firms operate internationally, the economic and cultural challenges they face, and the strategic decisions required to succeed in a global marketplace.